Association Between Antenatal Visit and Stunting in Children Aged 0-59 Months in Margadadi Health Center, Indramayu, West Java, Indonesia - Zahirah, Najma; Nugrohowati, Nunuk; Pramono, Andri Pramesyanti; Razi, Fachri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Stunting is a condition where a child's height does not match their age caused by persistent nutritional disorders. The incidence of stunting in the Indramayu area is quite high, namely 29.19% in 2019 which exceeds the WHO target of 20%. Antenatal visits indirectly induce stunting since stunting factors can be seen prenatally. Antenatal visits are a series of comprehensive examinations for pregnant women. The Indonesian Ministry of Health's 2021 recommendations divide antenatal visits into the first (K1), fourth (K4), and sixth (K6) visits. This study aimed to discover the relationship quantity of antenatal visits and the incidence of stunting in toddlers in the Margadadi Puskesmas Working Area, Indramayu Regency. Subjects and Method: A case-control study conducted at the Margadadi Community Health Center, Indramayu, West Java, Indonesia. A total of 60 moms of toddlers selected in this study use the consecutive sampling, with 30 subjects each as a case and control group. The dependent variable was stunting. The independent variables were ANC visit follow are K1, K4, and K6. Data collected by questionairre. Data were analyzed by Chi-Square test. Results: Pregnant women who had complete K6 antenatal visits had lower risk to have stunted children (OR= 0.20; 95% CI= 0.04 to 1.02; p= 0.038). Conclusion: K6 shows a protective relationship on stunting.